Factores histórico-sociales en la evolución de las ciudades latinoamericanas (1850-1950) - Ratinoff, Luis (Revista EURE - Revista de Estudios Urbano Regionales, 1982)
Theories about the spatial distribution of the population should consider historical factors explaning settlement growth patterns, geographic relationships between economic organizations and structures of domination. Urban concentration has been a region-wide phenomenon for one hundrer years, begining late XIX Century. However, the rol of the cities in the development processes has been more important in those countris where the oligarchy consolidated its domination earlier. Its role stems from the expansion of commercial and financial activities in detriment of artisan industries. In this sense they were parasite cities: the ruling classes were consimers rather than savers, rentists rather than producers. Two types of cities are considered in the paper: bastion cities and central cities. They were developed during the primary export period, from the middle of the las Century until the 1920s. In the bastion city the monetary economy was restricted to the city, economic surplus was spent or reinvented almost entirely in the city while the masses of the population were kept at subsistence levels in the rural areas. The ruling classes justified their domination as something functional to their self-assigned role of spreading the civilization over a "barbaric" national periphery. Thus the bastion city generated an authoritarian political structure. In other countries the central city gave place to a broader social demographic diffusion of modern values and a more dynamic and opener environment emerged. The oligarchies imposed themselves in a less authoritarian manner and did not opposed the growth of middle classes. A greater cultural and social continuity throughout a network of medium size and small cities spread towards the national peripheries. Industrialization policies that followed the crisis of the primary-export model implied subsidies to the major cities and therefore, encouraged the spatial concentration of population. Local life was undermined and the regions lost internal integration as a result of a reorganization of national territories imposed by the emerging industrial city. Industrialization processes implied a tacit social compromise between traditional social structures and the adoption of imported technologies, between the preservation of social thierarchies and pressures towards democratization. The timing of the industrial processes is a key factor in explaining the differences among countries with regard to social urban structures and to urban physical environment as shaped by the social elites, classes and masses. The later the industrial process occured the higher is the population density in the rural areas, the lesses is the initial rate of urbanization and the higher the rate of population growth in the large cities. Urban exploition accompanying the more recent industrialization processes in Latin America is often accompanied by social marginality and a caothic growth of the large cities.